(untitled) (KMC Journal, 2022)
This paper seeks to examine the issues of alienation, fragmentation, and the predicament of identity experienced by Mohun Biswas, the protagonist in V.S. Naipaul’s novel, A House for Mr. Biswas, from the perspective of post-colonialism. To uncover how Naipaul grapples with issues of post-colonialism such as dislocation, identity crisis, and longing for a sense of belonging in an alien world, the research tool taken for the investigation is post-colonialism, with special reference to Gayatri Chakravorty Spivak, Homi K. Bhabha, and Leela Gandhi. The research design used for the analysis is textual analysis. The principal finding is that Mr. Biswas, a representative of the novelist’s voice, resides in an alienated situation within his own community, despite the fact that he is physically residing with them. The paper focuses on key terms of postcolonial literature such as dislocation, identity crisis, and diaspora to diagnose the character’s attitudes towards the alienated lifestyle. The readers and scholars interested in researching diaspora literature in future are expected to take the paper as a reference.